2012
DOI: 10.1016/j.jadohealth.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Associations Among Body Mass Index, Body Dissatisfaction, and Weight and Shape Concern in Adolescent Boys and Girls

Abstract: Purpose To examine how the associations among BMI and body dissatisfaction and weight and shape concern evolve from late childhood through late adolescence in boys and girls. Methods We analyze data from 9–18-year-olds from the Growing Up Today Study, a national prospective cohort of U.S. Youth (n= 16,882, yielding 59,750 repeated measures observations during five waves of data collection). Generalized additive models produced curves of association for body dissatisfaction and weight concern across BMI perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
165
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(195 citation statements)
references
References 30 publications
22
165
2
6
Order By: Relevance
“…Another relevant aspect emerging from this study is that the risk of becoming underweight is also an important consideration, especially in the European population and particularly among girls. The different tendency of the two sexes to become underweight may be linked to a different perception of one's body image [37,38]. Gualdi-Russo et al [38], using the sample population from the same geographical area as the present study, reported that both sexes desired a thinner body image, with a higher degree of dissatisfaction among girls than boys.…”
Section: Discussionmentioning
confidence: 52%
“…Another relevant aspect emerging from this study is that the risk of becoming underweight is also an important consideration, especially in the European population and particularly among girls. The different tendency of the two sexes to become underweight may be linked to a different perception of one's body image [37,38]. Gualdi-Russo et al [38], using the sample population from the same geographical area as the present study, reported that both sexes desired a thinner body image, with a higher degree of dissatisfaction among girls than boys.…”
Section: Discussionmentioning
confidence: 52%
“…Longitudinal studies investigating the course of disordered eating from adolescence to young adulthood in the community are limited in number and have yielded heterogeneous results, most likely due to relatively small sample sizes, different study designs or selection of patients. Whilst several recent studies have demonstrated that ED and eating-disordered behaviour are stable from early adolescence to young adulthood [9][10][11], other previous studies did not find evidence of continuity of this behaviour in the majority of subjects [12,13]. In the majority of studies, continued eating-disordered behaviour was accompanied by a wide range of psychopathology and the development of obesity [11,12,14].…”
Section: Introductionmentioning
confidence: 95%
“…Most qualitative studies have described adolescents/adults’ experiences of obesity and body-image, and also adolescents’ perception of their body appearance and obesity and the same perception or views by the mothers/parents (Calzo et al, 2012; Lindelof et al, 2010; McCabe et al, 2011; Peyman et al, 2012; Pope et al, 2014; Sand, Emaus, & Lian, 2015; Shrewsbury et al, 2010; Spiller, 2009; Watt & Ricciardelli, 2012; Wills et al, 2006); also, a small number of studies have addressed the issue of height (Pope et al, 2014; Watt & Ricciardelli, 2012; Wills et al, 2006). The present study attempted to conduct a qualitative inquiry to understand the dimensions of an adolescent’s height/weight growth-based concerns among Iranian parents’ perspectives.…”
Section: Introductionmentioning
confidence: 99%